The challenges faced by women-owned companies in Afghanistan under COVID-19 and Taliban - Tayeba Hashemy; Rajeev Shrestha; Sayed Mahdi Hashemy; Yasuhiro Kotera; Yudai Kaneda; Divya Bhandari; Pratigya Dulal; Sudeepa Abeysinghe; Akihiko Ozaki; Sayed Hamid Mousavi (Cogent Social Sciences)
The COVID-19 pandemic and the shift of power to the Taliban have negatively affected women-owned companies. This study aimed to explore the external and internal challenges of women-owned businesses from March 2020 to January 2022 in Afghanistan. In-depth semi-structured interviews were conducted from December 2021 to January 2022 with 29 women-owned company owners and chief executive officers (CEOs) based in five provinces of Afghanistan. Data were analyzed using thematic analysis. The themes are COVID-19 external challenges: movement restriction, inability to access the market, and financial issues. COVID-19 internal challenges: financial and production problems. Taliban governance external challenges: regulation on women’s activities, economic crisis, and market downturn, and Taliban governance internal challenges: financial issues, production issues, and staff mental wellbeing. The study concluded that challenges due to the COVID-19 and Taliban governance presented strong shocks to women-owned companies that may precipitate the closure of these companies or the immigration of businesswomen.